1973
DOI: 10.1017/s0022112073001217
|View full text |Cite
|
Sign up to set email alerts
|

On the stability of plane Couette flow to infinitesimal disturbances

Abstract: It has been conjectured for many years that plane Couette flow is stable to infinitesimal disturbances although this has never been proved. In this paper we use a, combination of asymptotic analysis and numerical computation to examine the associated Orr-Sommerfeld differential problem in a systematic manner. We obtain new evidence that the conjecture is, in all probability, correct. In particular we find that, at a fixed large value of the Reynolds number R, as in an experiment, if a disturbance of wavenumber… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
30
0

Year Published

1975
1975
2024
2024

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(31 citation statements)
references
References 14 publications
1
30
0
Order By: Relevance
“…Evidently, the three-dimensional disturbances quickly achieve a form that grows exponentially in time for R < 1000. The growth rate of the threedimensional disturbances is rapid with their amplitude increasing by a factor of about 10 in a Here E 2D is the total energy (relative to the laminar flow) in wave numbers of the form (na 9 0) 9 while E 3D is the total energy in wave numbers (na f (3). For R £ 1000 we obtain growth and for R = 500 decay.…”
mentioning
confidence: 80%
See 2 more Smart Citations
“…Evidently, the three-dimensional disturbances quickly achieve a form that grows exponentially in time for R < 1000. The growth rate of the threedimensional disturbances is rapid with their amplitude increasing by a factor of about 10 in a Here E 2D is the total energy (relative to the laminar flow) in wave numbers of the form (na 9 0) 9 while E 3D is the total energy in wave numbers (na f (3). For R £ 1000 we obtain growth and for R = 500 decay.…”
mentioning
confidence: 80%
“…A similar problem was studied in Ref. 3, where profile steepening because of cavity formation could be predicted. However, the calculations were based on the driven nonlinear Schrodinger equation ignoring ion inertia.…”
mentioning
confidence: 81%
See 1 more Smart Citation
“…Numerical studies of the linear stability problem have been carried out by Grohne (1954), Gallagher andMercer (1962, 1964), Deardorff (1963), Davey (1973), and Gallagher (1974); however, all these studies found no evidence of instability. A number of analytic studies have also been carried out on this problem.…”
Section: Introductionmentioning
confidence: 99%
“…However, at large Reynolds number these modes fall into two classes. There are relatively slowly decaying modes concentrated in boundary layers next to the walls (Davey 1973) and there are rapidly decaying modes with oscillatory structure in the centre of the channel (Schmid et al 1992). The boundary modes are exponentially small in the main body of the flow, whereas the central modes are not localized within the defect region.…”
Section: The Viscous Problemmentioning
confidence: 99%